Carnivalization As a Way of Transmitting Socio-cultural Experience in the Era of Post-literacy - Vladimirova, Natalya; Kolmakova, Yevgeniya; Mezentsev, Yevgeniy; Mosienko, Liliya; Solomina, Natalya (KnE Social Sciences, 2020)
The aim of the research is to prove the possibility of transmitting socio-cultural experience between generations during the post-literacy period based on of carnivalization techniques, which are considered as a universal phenomenon that accumulates mythological beliefs and magical (mysterious) actions common to both art and Internet communication texts. This article examines such a feature of the transfer of experience between generations in modern society as pre-figurativeness, which shows the relationship of and relations between ”parents” and ”children” and the features of socialization in this culture (described as the so-called ”cyber-socialization”). The study, based on an analysis of classical literature texts (poetic texts by A. A. Akhmatova), as well as blogs on the livejournal.com and diary.ru platforms, shows that these different texts use speech masks that can identify both the poet and the Network user. The authors also conclude that Internet communication is a special space in which the problem of information security becomes relevant, which is understood through philosophical reflection and brought to the level of philosophical analysis. Keywords: post-literacy era, carnivalization techniques, socio-cultural experience, pre-figurativeness, information security